2020
DOI: 10.51153/mf.v15i2.459
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Mediating Role of Green Buying Behavior

Abstract: Sustainability of the environment is one of the major issues both in developed and developing countries. There is an abundance of studies on green buying behavior. However, a few have studied the mediating role of green buying behavior. Thus, we have developed a new model that has five direct and three mediating relationships. This empirical research has used a snowball sampling technique for collecting the data. We distributed 400 questionnaires and received 377 valid responses. The study has used Smart PLS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…Results from the analysis supported this hypothesis. These findings are in line with prior studies, which have indicated that consumers' behavior is frequently influenced by their social groups, and they would always want to associate with people who care about environmentally friendly products (Blose et al 2020;Geng et al 2017;Khalique et al 2020;Khare, 2019;Li & Wu, 2020;Thormann & Wicker, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Results from the analysis supported this hypothesis. These findings are in line with prior studies, which have indicated that consumers' behavior is frequently influenced by their social groups, and they would always want to associate with people who care about environmentally friendly products (Blose et al 2020;Geng et al 2017;Khalique et al 2020;Khare, 2019;Li & Wu, 2020;Thormann & Wicker, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The study results are also consistent with the findings of Blose et al (2020), who identified that social groups, acquaintances, neighbors, and family relationships play an essential role in cultivating recycling behaviors in the young US and Chinese consumers. This is further supported by Khalique et al (2020), who observed that social influence significantly impacts green purchasing behavior in a study on consumers' attitudes toward green consumerism in Pakistan. Furthermore, regardless of their positive attitudes, a lack of social influence from important people may prevent students from participating in this process of pro-environmental sustainability (Liao & Li, 2019).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The scales were adapted from existing green-buying behavior and sustainability marketing studies (Woo and Kim, 2019;Chen and Deng, 2016;Stojanova et al, 2021;Varela-Candamio et al, 2018;Zheng et al, 2020;Khalique et al, 2020;Watanabe et al, 2020). To ensure content validity, semantic and conceptual equivalence, and consistency of construct meaning among samples, the original English version of the survey underwent translation and subsequent back-translation by professional translators well versed in Portuguese.…”
Section: Measures Validity and Reliabilitymentioning
confidence: 99%